Species composition of small mammals in key biotopes near Kolomak (Kharkiv Oblast) - Oksana Markovska (Theriologia Ukrainica, 2020)
The study of the species composition and biotope preferences of small mammals around Kolomak had been carried out for four years (2017–2020). During the study period, 9 species of mouse-like rodents and 3 species of insectivores were found. No Cricetulus migratorius, Terricola subterraneus or Microtus oeconomus were found from the theoretically expected species already known for this area. Around Kolomak, 11 biotopes were investigated, including maple-linden oak forest, agrocenoses, dry and flooded meadows, which are located along the banks of a pond and in a gully-ravine system. The first year of research was in a year of high abundance (2017), and then 9 species were immediately discovered, but species with small abundance, such as Crocidura suaveolens, Sorex minutus, and Micromys minutus, were found in years with a small relative abundance of small mammals. Myodes glareolus, Sylvaemus tauricus and Sylvaemus uralensis are dominant species in the captures. According to the trapping results, 2017 was the year of high relative abundance of small mammals, 2018 was the year of the lowest relative abundance, 2019 and 2020 were years with an average relative abundance. During the study period, 6 species were identified in forest biotopes (Apodemus agrarius, Sylvaemus tauricus, Sylvaemus uralensis, Myodes glareolus, Sorex araneus, and Dryomys nitedula). In ecotones with floodplain biotopes, 8 species were found (Apodemus agrarius, Sylvaemus sylvaticus, Sylvaemus uralensis, Mus musculus, Micromys minutus, Myodes glareolus, and Sorex araneus). Four species (Mus musculus, Sylvaemus sylvaticus, Sylvaemus uralensis, and Microtus levis) were discovered near human settlements. In general, biotopes with the greatest species diversity and number of caught individuals are ecotones of dry and floodplain meadows. In years of high abundance, both species diversity and the number of individuals caught in the oak forest and in ecotones near the pond increased. It should be noted that Myodes glareolus was caught in clear-cuts during the two years (2019-2020) only in the summer of 2020. Earlier, not a single specimen of this species was caught there, although there is a dense weed grass cover in this area and the shrub layer has also grown up in some places, and the clear-cut is surrounded by oak forest.